Should universal distribution of high dose vitamin A to children cease?. (1st March 2018) - Mason, JB; Benn, CS; Sachdev, HPS; West, Keith P; Palmer, Amanda C; Sommer, Alfred
Abstract : Up to 500m a year could be put to better use by stopping ineffective and potentially harmful supplementation programmes in poorer countries, say JB Mason, CS Benn, and HPS Sachdev ; but Keith P West Jr, Amanda C Palmer, and Alfred Sommer disagree, saying that such programmes have been proved to save millions of lives and should be withdrawn only when robust evidence permits